Nonlinear dynamics of ferroelectrics with three-well local potential - Yevych, R.; Medulych, M.; Vysochanskii, Yu. (Condensed Matter Physics, 2018)
For Sn₂P₂S₆
ferroelectrics, the appearance of spontaneous polarization is related to stereoactivity of tin cations
and valence fluctuations of phosphorous cations. Here, the continuous phase transition and its behavior under
pressure is determined by thee-well local potential and can be described in an anharmonic quantum oscillator
model. For such a model, the spectrum of pseudospin fluctuations at different temperatures and pressures
has been calculated and compared with the data of Raman spectroscopy. It was revealed that the ferroelectric
lattice instability is related to several low energy optic modes. Для сегнетоелектрика Sn₂P₂S₆ поява спонтанної поляризацiї пов’язана зi стереоактивнiстю катiонiв олова та валентними флуктуацiями катiонiв фосфору. Неперервний фазовий перехiд та його поведiнка з
тиском визначається локальним триямним потенцiалом i описується в моделi ангармонiчного квантового осцилятора. Для такої моделi розрахованi спектри флуктуацiй псевдоспiна при рiзних температурах i
тисках, якi порiвнюються з даними раманiвської спектроскопiї. Показано, що нестiйкiсть сегнетоелектричної ґратки пов’язана з декiлькома низькоенергетичними оптичними модами.